2020
DOI: 10.1051/0004-6361/202037579
|View full text |Cite
|
Sign up to set email alerts
|

Influence of migration models and thermal torque on planetary growth in the pebble accretion scenario

Abstract: Low-mass planets that are in the process of growing larger within protoplanetary disks exchange torques with the disk and change their semi-major axis accordingly. This process is called type I migration and is strongly dependent on the underlying disk structure. As a result, there are many uncertainties about planetary migration in general. In a number of simulations, the current type I migration rates lead to planets reaching the inner edge of the disk within the disk lifetime. A new kind of torque exchange … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 73 publications
(208 reference statements)
0
15
0
Order By: Relevance
“…where Ṁpeb is the accretion rate of pebbles onto the planet (see below). Depending on the accretion efficiency of the planet, this thermal torque can lead to outward migration (Guilera et al 2019;Baumann & Bitsch 2020).…”
Section: Migrationmentioning
confidence: 99%
“…where Ṁpeb is the accretion rate of pebbles onto the planet (see below). Depending on the accretion efficiency of the planet, this thermal torque can lead to outward migration (Guilera et al 2019;Baumann & Bitsch 2020).…”
Section: Migrationmentioning
confidence: 99%
“…Recently Jiménez & Masset (2017) introduced a new torque formula, which includes the same effects, but should be more accurate, because it is based on 3D hydrodynamical simulations in contrast to Paardekooper et al (2011), which was based on 2D simulations. However, the changes compared to the Paardekooper et al (2011) torque formula seem quite small in the pebble accretion scenario (Baumann & Bitsch 2020). The accretion of material onto the planet can change the gas dynamics around it, leading to a thermal torque (Lega et al 2014;Benítez-Llambay et al 2015), which can, if the accretion rates are large, lead to outward migration (Benítez-Llambay et al 2015).…”
Section: Planetary Migrationmentioning
confidence: 99%
“…In addition, this effect could also increase the planetary eccentricity (Chrenko et al 2017). However, Baumann & Bitsch (2020) showed that these effects only become very important if the accretion rates onto the planet are very large. In fact, we do not reach the accretion rates needed for the thermal torque to become positive and thus ignore its effects in this work.…”
Section: Planetary Migrationmentioning
confidence: 99%
“…Planetary embryos that start to grow at 3 AU initially first migrate outward due to the effects of the heating torque (Benítez-Llambay et al 2015;Masset 2017;Baumann & Bitsch 2020) but then migrate rapidly inward before they open deep gaps. This is caused by the relatively long envelope contraction phase for these small cores.…”
Section: Planet Formationmentioning
confidence: 99%